Strategi Pengelolaan Keuangan Keluarga Secara Islami dalam Mewujudkan Keluarga yang Sakinah: Studi Kasus pada Masyarakat Desa Suka Makmur Kabupaten Muaro Jambi - Irma Dwi Pratiwi; Robiyatul Alawiyah; Arsa Arsa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted among the people of Suka Makmur Village, Muaro Jambi Regency, among whom work as farmers and traders. In the lean season, they still have to fulfill their daily needs, such as clothing, food and shelter. Apart from that, they also have to save and invest to meet future needs. This research aims to: (1) find out strategies for managing family finances in an Islamic way in creating a sakinah family. (2) knowing the supporting and inhibiting factors faced by the people of Suka Makmur Village, Muaro Jambi Regency in managing family finances in an Islamic manner in creating a sakinah family. This research uses a qualitative approach with the type of field research. Determining the research subjects was purposive and used data collection techniques through observation, interviews and documentation. The results of this research show that the Islamic family financial management strategy in creating a sakinah family in the Suka Makmur Village community, Muaro Jambi Regency has carried out financial planning such as managing family finances, savings, investment and zakat. Meanwhile, the supporting and inhibiting factors faced by the people of Suka Makmur Village, Muaro Jambi Regency in managing family finances in an Islamic manner in creating a sakinah family. Supporting factors are faced such as instilling mutual respect, providing support to your partner or family, and having a good personality such as being frugal. Meanwhile, factors such as wasteful nature, lack of communication, and economic problems.